Effects of Lower Limb Length and Body Proportions on the Energy Cost of Overground Walking in Older Persons - Vannetti, Federica (Hindawi Publishing Corporation, 2014)
Background. Although walking has been extensively investigated in its biomechanical and physiological aspects, little is known on whether lower limb length and body proportions affect the energy cost of overground walking in older persons. Methods. We enrolled 50 men and 12 women aged 65 years and over, mean 69.1 ± SD 5.4, who at the end of their cardiac rehabilitation program performed the six-minute walk test while wearing a portable device for direct calorimetry and who walked a distance comparable to that of nondisabled community-dwelling older persons. Results. In the multivariable regression model (F = 12.75, P < 0.001, adjusted R(2) = 0.278) the energy cost of overground walking, expressed as the net energy expenditure, in kg(−1) sec(−1), needed to provide own body mass with 1 joule kinetic energy, was inversely related to lower limb length and directly related to lower limb length to height ratio (β ± SE(β) = −3.72∗10(−3) ± 0.74∗10(−3), P < 0.001, and 6.61∗10(−3) ± 2.14∗10(−3), P = 0.003, resp.). Ancillary analyses also showed that, altogether, 1 cm increase in lower limb length reduced the energy cost of overground walking by 2.57% (95%CI 2.35–2.79). Conclusions. Lower limb length and body proportions actually affect the energy cost of overground walking in older persons.